Community Training in Jatimas Semarang Through Ethnobotany-Based Conservation and Utilization of Lerak (Sapindus rarak DC.) - Muhammad A'tourrohman; Muhammad Yusrun Niam; Malia Ulfah; Siti Faza Malianimah; Akhdan Najla Malik Al Abda; Siti Fatimah; Salsabiela Pertiwi; Mirtha Sari; Aziz Afrizal; Erna Wijayanti; Rusmadi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
Lerak (Sapindus rarak DC) has many benefits, including washing soap, vegetable pesticides, foaming agents for toothpaste, essential ingredients for soap gels, and antibacterial agents. Along with the many uses, it must be balanced with conservation activities to maintain the sustainability of lerak resources. This study aims to determine the usefulness of lerak (Sapindus rarak DC) and generative conservation efforts of lerak in the Jatimas community, Mijen, Semarang. This community service-based research was conducted in January-February 2021 in Jatimas, Mijen, Semarang. The research method uses the ethnobotany approach, conservation, and literature study, which is equipped with interviews and direct observations. The results show that the community uses lerak as herbal soap, jewelry washing agent, and insecticide. Through this community service program, the community has carried out generative conservation of lerak through seeds.